Acesso e representação das formas nominais flexionadas em número em português brasileiro: um estudo sobre o léxico mental. - Rocha, Jefferson Alves da (2016)
This dissertation aims to understand and analyze the lexical relations existing in the processing of regular words inflected in number in Brazilian Portuguese (BP), as well as to suggest a model of representation for these kind of words. We observed how words inflected in number are stored in and retrieved from the mental lexicon. Recent psycholinguistic studies have pointed out that factors like base frequency influence the processing time of forms inflected both in gender and number (DOMINGUEZ; CUETOS; SEGUI, 1999). Specifically regarding to gender inflection in BP, a frequency effect of gender inflected dominant form has been found (CORRÊA; ALMEIDA; PORTO, 2004). This experiment was carried out in order to provide some evidence about if the frequency of dominant form affects the forms inflected in number, similarly to the forms inflected in gender. The experimental design consisted of a word reading task in which both the base frequency and the frequency of dominant form inflected in gender were controlled. The results were similar to the ones found by Corrêa, Almeida e Porto (2004), since the singular words were retrieved in its whole form and the plural words were retrieved by lexical decomposition, excepting the cases of plural forms with high level of frequency, that also behave as singular forms. These results evidence the way how the inflected words are stored in the mental lexicon of BP speakers, as well as to describe its organization from a linguistic and psycholinguistic point of view.